Assessing Iraqi Learners' Perceptions and Attitudes through Reading Literary Texts - Qayssar Abbas Abdulridha (Taez University, 2023)
The purpose of this paper is to assess how reading literature has affected the cultural experiences of Iraqi students. This study was conducted among third-year students at the department of English and literature to evaluate their cultural background in reading literature. The responses of the students to reading literature were compiled using a survey to gather data. The study involved asking a minimum of 42 Iraqi students, with 86% of the respondents being female and 14% male. The researcher employed closed-ended questions from a questionnaire in order to gather information about the students' literary reading experiences. A variety of statistical tools were used to analyze the data. The study's outcomes (Mean=3.63) show that Iraqi students' experiences and attitudes were accepted to a full degree as a result of reading literary texts. According to the results of a survey on the cultural experiences and personal information through reading literature, the majority of Iraqi students have favorable attitudes and positive perceptions toward reading literature. The majority of students choose literary texts over non-literary ones when reflecting on their own experiences, attitudes, or observations, as well as on past experiences, present needs, and connections to the text's ideas.